Analysis of Language Errors at the Morphological Level in Students’ Papers at the Islamic University of Riau - Rika Afriana; Tri Yuliawan (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Language errors are the ignorance of individuals or groups of people about the basic concepts of language learning, the result of this ignorance will cause deviations from the determining factors of communication or social norms as well as deviations from applicable grammatical rules. There are still errors in the student papers of the Indonesian Language and Literature Education Study Program, Riau Islamic University. This error is seen at the morphological level. Therefore, this research was carried out with the aim of identifying errors in students' papers at the morphological level. The method used in this research is a content analysis method with a qualitative approach. Data collection techniques use documentation techniques, reading techniques and note-taking techniques. In this study, the author found 81 errors including 4 errors in omitting affixes, 24 errors in sounds that should have melted but were not melted, 3 errors in decaying sounds that should not have melted, 4 errors in replacing morphs, 2 errors in abbreviating morphs mem-, men-, meng-, meny-, and menge-, 23 errors in inappropriate use of affixes, 2 errors in determining the base form incorrectly, 6 errors in inappropriate affixes in word combinations, and 2 errors in inappropriate repetition of compound words.